Consumer liking, purchase intent, and willingness to pay for Lupinus mutabilis Sweet in relation to debittering treatments. (March 2015) - Carvajal-Larenas, F.E.; Koziol, M.; Linnemann, A.R.; Nout, M.J.R.; van Boekel, M.A.J.S.
Highlights: Lupinus mutabilis debittering processes were studied from consumers' perspective. Relationships between processing, liking, price and W.T.P. were quantified. Data obtained was used for modeling and optimizing by a new approach. Managers can use the findings for selecting best product and pricing practices. The approach used in this study can also be applied to other products. Abstract: Interrelationships between food processing conditions, consumer liking, purchase intent and willingness to pay can be studied and modeled as exemplified by this paper on lupin ( Lupinus mutabilis ). Lupin was debittered by 12 different aqueous treatments and evaluated by 99 consumers. First they scored the products on the basis of liking. Next, they were informed about the price of the products and asked to rank their purchase intent in relation to their liking scores and product price. Treatments with more processing (i.e. longer agitation times and/or more frequent changes of water) increased the product price but diminished liking. Consumers did not choose between liking and price; the purchase intent was the combined effect of both variables. Willingness to pay was inferred from the purchase intent plot. For example, at a purchase intent of 2, consumers would accept an increase in price of 0.3 $/kg if liking increased from "like slightly" to "like moderately". In the studied range, the effect of processing on liking and expected price, as well as their effect on purchase intent, could be described by first order regression equations.